2021
DOI: 10.1016/j.ijid.2021.03.008
|View full text |Cite
|
Sign up to set email alerts
|

Meta-analysis of cardiac markers for predictive factors on severity and mortality of COVID-19

Abstract: Objective Previous observational studies suggested that increased cardiac markers are commonly found in COVID-19. This study aimed to determine the relationship between several cardiac markers and the severity/mortality of COVID-19 patients. Methods We analysed several cardiac markers in this meta-analysis. RevMan 5.4 was used to provide pooled estimates for standardized mean difference (SMD) with 95% confidence intervals. Results Twenty nine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
24
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(36 citation statements)
references
References 65 publications
(47 reference statements)
2
24
0
1
Order By: Relevance
“…In the current study, laboratory parameters indicating increased risk of severe COVID-19 such as N/L ratio and CRP were identical in both groups, but D-dimer and IL-6 levels were higher on admission in the second wave. It has previously been suggested by Wungu et al, in a meta-analysis comparing cardiac markers as predictive factors in COVID-19 infection that the D-dimer level was the best predictor of severity and mortality [13]. IL-6 levels were also shown to be significantly elevated in patients with severe disease relative to those with less severe disease.…”
Section: Discussionmentioning
confidence: 81%
“…In the current study, laboratory parameters indicating increased risk of severe COVID-19 such as N/L ratio and CRP were identical in both groups, but D-dimer and IL-6 levels were higher on admission in the second wave. It has previously been suggested by Wungu et al, in a meta-analysis comparing cardiac markers as predictive factors in COVID-19 infection that the D-dimer level was the best predictor of severity and mortality [13]. IL-6 levels were also shown to be significantly elevated in patients with severe disease relative to those with less severe disease.…”
Section: Discussionmentioning
confidence: 81%
“… 135 In another recently published article, high concentrations of CK‐MP, procalcitonin, NT‐proBNP, BNP, troponin, and D‐dimers have been shown to predict severity and survival for patients with COVID‐19 as well. 136 Several other studies have confirmed the relationship between high troponin values and a worse prognosis in patients with COVID‐19 infection. 126 , 137 , 138 , 139 It is still not clear whether this relationship is due to a more severe form of COVID‐19 or to a more extensive cardiac damage or both.…”
Section: Covid‐19 Infection and Cardiac Biomarkersmentioning
confidence: 87%
“…BNP was recently described in the meta-analysis by Wungu et al [ 11 ] as a possible predictive marker for survival of COVID-19 patients. A significant difference between surviving and non-surviving patients was reported in our study as well, but BNP was eventually outperformed by NT-proBNP and HsTnI ROC curves.…”
Section: Discussionmentioning
confidence: 99%
“…NT-proBNP is currently known as an independent risk factor for in-hospital death of patients with severe COVID-19 [ 10 ]. B-type natriuretic peptide (BNP) was recently reported as a possible predictive marker for survival of COVID-19 patients [ 11 ]. HsTnI is significantly increased at admission in patients with severe COVID-19 compared to those affected by milder forms of COVID-19 [ 12 ], and has been recently described as a possible predictor of in-hospital mortality [ 13 ].…”
Section: Introductionmentioning
confidence: 99%